La cosa e L’Uno. Luoghi e itinerari cacciariani - Nicola Magliulo (Lo Sguardo - Rivista di Filosofia, 2014)
In this paper we illustrate some of the theoretical fundamentals of the route nodes speculative Massimo Cacciari. How can you define the absolute singularity of the thing; what implies that the mere possibility is that from which it comes; what relation is given between the One and the negative of the world; what are the limits of logos: these and other issues are addressed from the last work of Cacciari, Maze philosophical, and in dialogue with thinkers like Heidegger and Severino, of which we show the similarities and differences with the theses of the Venetian philosopher.